Nannorrhops ritchieana (Griff.) Aitch. (Arecaceae) - a traditional multipurpose plant species of Pakistan - Ali, Maroof; Hussain, Khateeb; Ullah, Manzoor; Ali, Usman; Ullah Khan, Saad; Bussmann, Rainer W; Joyal, Elaine; Shao, Jian-Wen (Ethnobotany Research and Applications, 2020)
Background: Traditional knowledge pertaining to the indigenous uses of N. ritchieana has been poorly documented, despite the ethnobotanical studies conducted in various parts of Pakistan. This report comprises traditional knowledge pertaining to the use of N. ritchieana in Tribal District Kurram, Pakistan. Methods:Ethnobotanical information on N. ritchieana use was obtained by interviewing 50 Mazari product manufacturers in Tribal District Kurram at four locations; Parachinar, Sadda, Ali Zai and Bagan. For this purpose, a semi-structured questionnaire was set. Prior informed consent was obtained from every participant.The data was quantitatively analyzed through relative frequency of citation (RFC), informant consensus factor (ICF) and cultural importance index (CI). Results: N. ritchieana is widely used in Pakistan and has been recognized as a traditional multipurpose plant species with socioeconomic, cultural, medicinal, religious, and spiritual values. The leaves of this species have been used in the manufacture of a variety of household items, especially mats, trays, baskets, bread pot, grain bins, cordage, chair, hand fan, and brooms. The fruit are eaten. The leaves and fruit are used medicinally. The palm is a symbol of “fruitfulness” and of “prosperity” and is planted in graveyards and religious places. It is also used for shade and, given its charismatic crown; it is cultivated for ornamental purposes. It is also important for apiculture. Conclusions: Documentation of traditional use and economic value of N. ritchieana is beneficial, not only for the indigenous people of the area but also for the country as a whole. There is a dire need to develop sustainable harvest and management of this species to preserveits use for future generations and to prevent itsextinction. Keywords: Traditional use, Nannorrhops ritchieana, Arecaceae, economic value, TribalrDistrictrKurram